The Effect of Static Electricity on Electronic Devices and How to Prevent It - Julianus Gesuri Daud; Sarah Getroida Rumondor; Jilf Frezzy Forland Tuerah; Michael Mandagi; Khairil Sandre; Daniel Tuerah (Syntax Corporation Indonesia, 2024)
Static electricity is a common phenomenon that occurs due to the imbalance of electric charges on the surface of materials. This imbalance can lead to the generation of electrostatic discharge (ESD), which has the potential to damage sensitive electronic devices. The impact of static electricity on modern electronics has become a growing concern as electronic devices become smaller and more intricate. This research examines the effects of static electricity on various electronic devices, including computers, smartphones, and other household appliances. It explores how static discharge occurs, the damage it causes, and, importantly, the methods to prevent or mitigate such damage. Various techniques and technologies, including the use of antistatic wrist straps, mats, and humidity control, are evaluated for their effectiveness in minimizing static buildup and discharge. The findings of this study aim to provide practical solutions for protecting electronic devices from static electricity, ultimately enhancing the longevity and reliability of electronic devices in everyday use.minimized in a safer and more efficient environment .